Analisis minat perbankan dalam keuangan berkelanjutan - Gumantiny, Melissa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Sustainable financial is one of the financial programs created by Otoritas Jasa Keuangan for supporting sustainable development. With this program, it is expecting to encourage companies to participate in sustainable development, this can be seen from one of the main requirments regarding to the operational activities that conduct by the company's for not damaging the environment. This research is written to know the banking interest regarding sustainable finance program from before and after the banking have the requirment for implementing the program. The research method that used for this research is quantitative analysis and for the approach is using descriptive approach. The result of this research will show that banking in Indonesia, especialy banking that have been registered in Bursa Efek Indonesia (BEI) with BUKU 3 and BUKU 4 category, having concern on sustainable financing program before the regulation confirmation. In 2015 and 2016 this concern have been increasing, and experience an increase, and have been experience a significant increasing after adding the regulation in 2017. This showed a low interest before the regulation has been added, just the attention for studying and planning.